2001
DOI: 10.1017/s0014479701003106
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Evaluation by Farmers of on-Farm Seed Priming in Wheat in India, Nepal and Pakistan

Abstract: The mean time for 50% germination at 20 8C of 12 Indian wheat (Triticum aestivum) cultivars was nearly halved, from 51 h to 27 h, by soaking seed in water for 8 h prior to sowing. A delay of 24 h without further soaking, intended to simulate postponement of sowing, reduced the time saved by priming to 16%. Priming had no effect on ®nal germination percentage. These results were used in the design of 275 on-farm, farmer-managed, participatory trials of seed priming in wheat during the 1997±98 and 1998±99 rabi (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
0
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 6 publications
(18 reference statements)
11
84
0
8
Order By: Relevance
“…Highest grain yield was obtained from the variety Manakamana 5 both in primed (5449 kg ha-1 ) and non-primed (4890 kg ha-1 ) environments. Our research findings from both mother and baby trials conducted at nine sites in three districts of Nepal agreed and supported the findings of previous research results carried out in various countries that direct benefits of seed priming in maize are faster emergence, better and more uniform stands, less need to re-sow, more vigorous plants, earlier flowering, earlier harvest and higher and stable grain yield (Chivasa et al, 1998;Harris et al, 1999Harris et al, , 2001bHarris et al, , 2002Rashid et al, 2002). These results were confirmed for maize in Pakistan and Zimbabwe (Harris et al, 1999.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Highest grain yield was obtained from the variety Manakamana 5 both in primed (5449 kg ha-1 ) and non-primed (4890 kg ha-1 ) environments. Our research findings from both mother and baby trials conducted at nine sites in three districts of Nepal agreed and supported the findings of previous research results carried out in various countries that direct benefits of seed priming in maize are faster emergence, better and more uniform stands, less need to re-sow, more vigorous plants, earlier flowering, earlier harvest and higher and stable grain yield (Chivasa et al, 1998;Harris et al, 1999Harris et al, , 2001bHarris et al, , 2002Rashid et al, 2002). These results were confirmed for maize in Pakistan and Zimbabwe (Harris et al, 1999.…”
Section: Discussionsupporting
confidence: 89%
“…There has been much research during the last several years to test, develop and promote on-farm seed priming in a range of crops, countries and agro-environments. The beneficial effects of seed priming on crop establishment, development and yield have been documented (Parera and Cantliffe, 1994;Chivas et al, 1998;Kulkarni and Eshanna, 1998;Harris et al, 1999Harris et al, , 2001aHarris et al, , 2001bHarris et al, , 2002Anonymous, 2002;Jasi et al, 2000;Krishi, 2058). Currently, seed priming research is ongoing in Bangladesh, Cameroon, Cote d'Ivoire, Gambia, Ghana, India, Kenya, Nigeria, Pakistan, Sierra Leone, Thailand and Zimbabwe.…”
Section: Introductionmentioning
confidence: 98%
“…Similar to other priming techniques, hydropriming generally enhances seed germination and seedling emergence [24]. This simple, low-cost, low-risk intervention also had positive impacts on the wider farming system and livelihoods and the technology has proved highly popular with farmers [25]. In the present work, we noticed that hydropriming does not improve the germinative quality of cucumber seeds treated or no with toxic doses of copper.…”
Section: Discussionmentioning
confidence: 46%
“…Heckel (1964); Scotte et al (1973); Harris et al (2001c) reported that early emergence from primed seed might have enhanced yield by increasing the amount of light intercepted by the canopy. Farooq et al (2006) is in agreement that osmo-hardening improved germination, emergence and yield of rice crop.…”
Section: Emergencementioning
confidence: 99%